Algorithm for Investigation of Fabry Disease in Cardiomyopathies - Sandra Marques e Silva; Ândrea V. F. Chaves; Murillo O. Antunes; Natalia R. Roque; Eduarda M. S. Montenegro; Isabelle Malbouisson; Maurício A. de Paula; Edileide B. Correia (Journal of Inborn Errors of Metabolism and Screening, 2024)
Abstract Fabry disease (FD) is a rare, x-linked lysosomal storage disease caused by mutations in the GLA gene that leads to total or partial alfa galactosidase A deficiency. Its prevalence ranges between 1:117,000 and 1:8,454. Mutations in the GLA gene result in alpha galactosidase A deficiency leading to the progressive accumulation of globotriaosylceramide (Gb3) in lysosomes of different types of cells of the heart, kidneys, skin, eyes, central nervous system, and gastrointestinal system, and may lead to different clinical scenarios. The cardiac manifestation most frequently found in FD is the presence of left ventricular hypertrophy (LVH) in a concentric pattern, although asymmetric forms are also reported. In clinical practice, it is often difficult to differentiate between FD and other diseases associated with LVH. In adults with LVH, a prevalence of FD of 3-5% has been reported. Therefore, diagnosing these patients is of fundamental importance, as specific treatment for FD has the potential to change the prognosis, especially if instituted early. The purpose of this article is to describe an algorithm developed through a thorough literature review to assist in the identification of FD in patients with cardiomyopathies.